Ceramic shell as well as preparation method and application thereof

By using low-sodium electromelting white corundum powder, active α-Al2O3 micro powder and calcined zircon powder in the ceramic shell, and adding enhancers, the problems of low high-temperature strength and poor heat dissipation of the ceramic shell are solved, and higher high-temperature strength and breathability are achieved, and the metallurgical quality of the castings is improved.

CN119657847APending Publication Date: 2025-03-21GAONA AERO MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891948.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the casting of single crystal high-temperature alloys, the existing ceramic molded shells have low high-temperature strength and excessive thickness of the molded shells, resulting in steel leakage and poor heat dissipation in weak areas, resulting in metallurgical quality defects.

Method used

Low-sodium electromelting white corundum powder and active α-Al2O3 micro powder are used as surface layer components, calcined zircon powder is used as back layer mineralizer, and the wet strength and high-temperature breathability of the ceramic shell are improved by enhancing agents, and the thickness of the shell is reduced to improve the heat dissipation performance.

Benefits of technology

It significantly improves the high-temperature strength and breathability of the ceramic shell, reduces the risk of steel leakage, improves the heat dissipation performance, and improves the metallurgical quality of single crystal high-temperature alloy castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657847A_ABST
    Figure CN119657847A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of precision casting, in particular to a ceramic shell and a preparation method and application thereof. The preparation method of the ceramic shell comprises the following steps: (a) coating a fired mold module with surface layer slurry, spraying sand, and drying to form a surface layer; (b) carrying out N times of back layer slurry coating, sand spraying and drying treatment on the surface layer to form a back layer; sealing slurry to obtain a wet blank; n > = 2; (c) dewaxing and roasting the wet blank; the surface layer slurry comprises a first binder, low-sodium fused white corundum powder, active alpha-Al2O3 micro powder and a first reinforcing agent; the back layer slurry comprises a second binder, low-sodium fused white corundum powder, calcined zircon powder and a second reinforcing agent; the first reinforcing agent and the second reinforcing agent comprise polyvinyl alcohol, polyacrylamide and water. The ceramic shell has chemical stability, high-temperature strength, high heat dissipation performance, high-temperature air permeability and the like, and can meet the production requirements of single-crystal high-temperature alloy turbine blades.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of precision casting, and in particular to a ceramic shell and a preparation method and application thereof. Background Art

[0002] Near-net-shape investment casting technology is currently the main technology for manufacturing high-temperature alloy components of hot-end aircraft engines such as turbine blades and integral casings. Among them, the preparation of ceramic shell materials with excellent performance is the prerequisite for the successful application of this technology. The high-temperature alloy casting process has high requirements on the strength, deformation resistance, air permeability, chemical and thermal stability of the ceramic shell, especially the single-crystal high-temperature alloy turbine blade casting process, which is more demanding to ensure the realization of its process.

[0003] At present, silica sol corundum shell is generally used as a single crystal high temperature alloy casting ceramic shell, such as EC95 shell. In the actual production of aircraft engine turbine blades, due to the low high temperature strength of the existing ceramic shell, in order to ensure that the shell has sufficient bearing capacity, the ceramic shell generally adopts a 6+1 or 7+1 layer coating process, which makes the average thickness of the existing single crystal ceramic shell generally reach 6-9mm, resulting in large heat storage and slow heat dissipation of the shell, which is not conducive to the temperature gradient control during the single crystal drawing process. Especially at the R angle position of the blade crown or trailing edge where the shell is the thickest, the slow heat dissipation causes the alloy temperature in this area to be too high, which is prone to metallurgical defects such as looseness, reducing the qualified rate of the blade. In addition, in some structural parts with small gaps, due to the low strength of the shell, steel leakage is prone to occur; at the same time, the existing shell raw materials and added mineralizers contain a small amount of impurities such as NaO2 and Fe2O3, which leads to the appearance of low-melting spots on the surface of the shell, which are prone to interface reaction with the alloy during the casting process, resulting in metallurgical defects such as sand sticking and inclusions.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a ceramic shell and a preparation method and application thereof. The ceramic shell of the present invention has chemical stability, high-temperature strength, high heat dissipation, high-temperature air permeability, etc., and is suitable for the manufacture of single-crystal high-temperature alloy castings. It can ensure the realization of the single-crystal alloy casting process and the improvement of the metallurgical quality of the castings, and can meet the production needs of single-crystal high-temperature alloy turbine blades.

[0006] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a method for preparing a ceramic shell, comprising the following steps:

[0007] (a) coating the surface layer slurry on the investment mold group, then pouring sand and drying to form the surface layer;

[0008] (b) coating the surface layer with a backing layer slurry, sprinkling sand, and drying the surface layer N times to form a backing layer; and sealing the slurry to obtain a wet blank; N≥2;

[0009] (c) dewaxing and calcining the wet blank to obtain the ceramic shell;

[0010] The surface layer slurry includes the following components by weight: 10 parts of a first binder, 25 to 38 parts of low-sodium fused white corundum powder, 1 to 2 parts of active α-Al2O3 powder and 0.2 to 1.5 parts of a first reinforcing agent;

[0011] The backing layer slurry comprises the following components by weight: 10 parts of a second binder, 15 to 25 parts of low-sodium fused white corundum powder, 1 to 5 parts of calcined zircon powder, and 0.2 to 1.5 parts of a second reinforcing agent;

[0012] The first reinforcing agent and the second reinforcing agent each independently include polyvinyl alcohol, polyacrylamide and water.

[0013] In a specific embodiment of the present invention, in the first enhancer and the second enhancer, the mass ratio of the polyvinyl alcohol to the polyacrylamide is independently 1:(1-5).

[0014] In a specific embodiment of the present invention, the first reinforcing agent and the second reinforcing agent each independently include, by mass percentage, 4% to 6% polyvinyl alcohol, 14% to 16% polyacrylamide and 78% to 82% water.

[0015] In a specific embodiment of the present invention, the particle size of the low sodium fused white corundum powder is 1-70 μm, and the sodium oxide content is less than 0.1 wt %. Furthermore, the aluminum oxide content of the low sodium fused white corundum powder is greater than 99.5 wt %.

[0016] In a specific embodiment of the present invention, the particle size of the active α-Al2O3 powder is 0.5-10 μm. Furthermore, the purity of the active α-Al2O3 powder is greater than 99.5 wt%.

[0017] In a specific embodiment of the present invention, the particle size of the calcined zircon powder is 2-50 μm. Furthermore, in the calcined zircon powder, the sum of the contents of ZrO2 and HfO2 is greater than 65 wt%.

[0018] In a specific embodiment of the present invention, the first binder includes silica sol. Further, in the first binder, the SiO2 content is 28wt% to 31wt%, the micelle diameter is 8 to 16μm, and the pH value is 9 to 10.5.

[0019] In a specific embodiment of the present invention, the second binder includes silica sol. Further, in the second binder, the SiO2 content is 20wt% to 30wt%, the micelle diameter is 8 to 20 μm, and the pH value is 9 to 10.5.

[0020] In a specific embodiment of the present invention, the surface layer slurry and the back layer slurry each independently include a defoamer and / or a wetting agent. Further, the amount of the defoamer and the wetting agent is 0.05-0.1 parts by weight and 0.02-0.08 parts by weight, respectively.

[0021] In a specific embodiment of the present invention, the coating-4 cup viscosity of the surface layer slurry is 25 to 50 seconds.

[0022] In a specific embodiment of the present invention, the coating-4 cup viscosity of the backing layer slurry is 10 to 30 seconds.

[0023] In a specific embodiment of the present invention, the surface layer of the glazing sand is white corundum sand. Further, the granularity of the surface layer of the glazing sand is 80-100 meshes.

[0024] In a specific embodiment of the present invention, the backing layer of the glazing sand is white corundum sand. Further, the granularity of the backing layer of the glazing sand is 16-60 mesh.

[0025] In a specific embodiment of the present invention, in the sanding of the back layer, the mesh number of the white corundum sand used in the first layer of sanding is greater than the mesh number of the white corundum sand used in the second layer of sanding.

[0026] In a specific embodiment of the present invention, during the calcination, the temperature is 850-1050° C. and the time is 3-6 hours.

[0027] A second aspect of the present invention provides a ceramic shell, which is prepared by the method for preparing a ceramic shell described in any one of the first aspects.

[0028] The third aspect of the present invention provides the use of the ceramic shell according to the second aspect in manufacturing single crystal high temperature alloy turbine blades.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) In the surface layer slurry and back layer slurry for preparing the ceramic shell of the present invention, α-Al2O3 micropowder and calcined zircon powder are respectively used as the sintering aid and mineralizer of the surface layer, and a certain amount of reinforcing agent is used in combination with the other components, which can significantly improve the wet strength and high temperature strength of the ceramic shell, reduce the risk of steel leakage in the weak part of the shell, provide conditions for thinning the shell, improve the heat dissipation performance, and significantly reduce metallurgical defects such as loose castings caused by temperature gradient control problems; at the same time, the organic polymer in the reinforcing agent is burned out to form pores during the roasting process, which can further improve the air permeability of the ceramic shell, help to remove the gas generated during the casting process, and further improve the quality of the casting molding of the single crystal high-temperature alloy;

[0031] (2) The present invention adopts low-sodium fused white corundum powder as the main raw material of the mold shell, and uses active α-Al2O3 micropowder with low impurity content as a surface layer sintering aid, thereby avoiding the formation of high-temperature low-melting products due to the introduction of excessive impurities, thereby improving the high-temperature strength of the mold shell, ensuring the high chemical stability of the mold shell surface layer, reducing the interface reaction between the mold shell surface layer and the alloy solution at high temperature, eliminating chemical sand adhesion and inclusions, and improving the surface quality of single-crystal high-temperature alloy turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 A process flow chart for preparing a ceramic shell according to an embodiment of the present invention;

[0034] Figure 2 This is a thickness comparison diagram of the ceramic shell prepared in Example 1 of the present invention and the EC95 shell of Comparative Example 1;

[0035] Figure 3 The actual photograph (a) and the fluorescent photograph (b) of a single crystal blade cast by using the ceramic shell prepared in Example 1 of the present invention;

[0036] Figure 4 The actual photo (a) and fluorescent photo (b) of the single crystal blade cast by using the EC95 ceramic shell of Comparative Example 1. DETAILED DESCRIPTION

[0037] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0038] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0039] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0040] The high-temperature alloy casting process has high requirements for the strength, deformation resistance, air permeability, chemical and thermal stability of the ceramic shell, especially the single-crystal high-temperature alloy turbine blade casting process, which is more demanding and requires the shell to have higher refractoriness, chemical and thermal stability, better high-temperature strength, thermal conductivity and air permeability. However, the ceramic shell used for single-crystal high-temperature alloy turbine blade casting currently has low high-temperature strength, and the shell is too thick, resulting in steel leakage in weak parts and poor heat dissipation, which leads to serious metallurgical quality defects.

[0041] Based on this, the present invention provides a method for preparing a ceramic shell having chemical stability, high-temperature strength, high heat dissipation, and high-temperature air permeability.

[0042] A first aspect of the present invention provides a method for preparing a ceramic shell, comprising the following steps:

[0043] (a) coating the surface layer slurry on the investment mold group, then pouring sand and drying to form the surface layer;

[0044] (b) coating the surface layer with a backing layer slurry, sprinkling sand, and drying the surface layer N times to form a backing layer; sealing the slurry, and drying to obtain a wet blank; N≥2;

[0045] (c) dewaxing and firing the wet blank to obtain a ceramic shell;

[0046] The surface slurry includes the following components by weight: 10 parts of a first binder, 25 to 38 parts of low-sodium fused white corundum powder, 1 to 2 parts of active α-Al2O3 powder and 0.2 to 1.5 parts of a first reinforcing agent;

[0047] The backing layer slurry includes the following components by weight: 10 parts of a second binder, 15 to 25 parts of low-sodium fused white corundum powder, 1 to 5 parts of calcined zircon powder, and 0.2 to 1.5 parts of a second reinforcing agent;

[0048] The first reinforcing agent and the second reinforcing agent each independently include polyvinyl alcohol, polyacrylamide and water.

[0049] The present invention uses low-sodium fused white corundum powder with low impurity content as the main raw material of the shell coating, uses active α-Al2O3 micropowder as the surface layer sintering agent, and calcined zircon powder as the back layer mineralizer to improve the chemical stability and high-temperature strength of the ceramic shell, reduce the chemical reaction between the high-temperature alloy molten metal and the shell surface layer at high temperature, and reduce the thickness of the shell to improve the heat dissipation performance while ensuring sufficient bearing capacity. At the same time, by adding an appropriate amount of organic polymer, the wet strength and high-temperature air permeability of the surface layer are improved.

[0050] In the surface slurry of the present invention, the amounts of the remaining components, compared to 10 parts by weight of the first binder, can be as follows:

[0051] The dosage of low sodium fused white corundum powder can be 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts or any two of them; the dosage of active α-Al2O3 powder can be 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts or any two of them; the dosage of the first reinforcing agent can be 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts or any two of them. In this way, the various properties of the ceramic shell can be fully improved.

[0052] In the backing layer slurry of the present invention, the amounts of the remaining components, compared to 10 parts by weight of the second binder, can be as follows:

[0053] The amount of low sodium fused white corundum powder can be 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or any two of them; the amount of calcined zircon powder can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts or any two of them; the amount of the second reinforcing agent can be 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts or any two of them. In this way, the various properties of the ceramic shell can be fully improved.

[0054] For example, in different embodiments, N may be 2, 3, 4, 5, 6, 7, 8, etc. The specific method for forming the back layer may include: (1) coating the back layer slurry on the surface layer, sprinkling sand, and drying; (2) repeating step (1) N-1 times. That is, each time the back layer slurry is coated, the sprinkling sand and drying steps are performed.

[0055] In a specific embodiment of the present invention, back layer slurry is used for slurry sealing. Specifically, slurry sealing includes: coating the back layer slurry on the back layer and drying.

[0056] Figure 1 A process flow chart for preparing a ceramic shell provided in an embodiment of the present invention. Specifically, the surface layer slurry and the back layer slurry can be prepared respectively according to the composition of the surface layer slurry and the back layer slurry, and then the surface layer slurry is coated on the investment mold group, and after the surface layer slurry is evenly coated on the investment mold group, it is sprinkled with sand and then dried. Then, the back layer slurry is coated on the surface layer, and after the back layer slurry is evenly coated on the surface layer, it is sprinkled with sand and then dried; the aforementioned steps of coating the back layer slurry, sprinkling sand, and drying can be repeated several times according to actual needs; then the back layer slurry is used to seal the slurry, and the wet blank is dried. The wet blank is then dewaxed and fired to obtain a ceramic shell.

[0057] In a specific embodiment of the present invention, in the first reinforcing agent and the second reinforcing agent, the mass ratio of polyvinyl alcohol and polyacrylamide is independently 1: (1-5), for example, it can be 1: 1, 1: 2, 1: 3, 1: 4, 1: 5, thereby ensuring the balance between the wet strength, high temperature strength and air permeability of the ceramic shell. Among them, the weight average molecular weight of polyvinyl alcohol is 20,000 to 150,000, for example, 20,000, 40,000, 60,000, 80,000, 100,000, 120,000, 150,000 or any two thereof, and the weight average molecular weight of polyacrylamide is 6 million to 12 million, for example, 6 million, 8 million, 10 million, 12 million or any two thereof. In the subsequent embodiments, polyvinyl alcohol with a weight average molecular weight of about 80,000 and polyacrylamide with a weight average molecular weight of about 8 million are used as examples for illustration, but are not limited thereto.

[0058] In a specific embodiment of the present invention, the first reinforcing agent and the second reinforcing agent each independently include, by mass percentage, 4% to 6% polyvinyl alcohol, 14% to 16% polyacrylamide and 78% to 82% water.

[0059] For example, in different embodiments, the amounts of the components in the first reinforcing agent and the second reinforcing agent can be as follows, respectively, by mass percentage:

[0060] The amount of polyvinyl alcohol can be 4%, 4.5%, 5%, 5.5%, 6% or any two thereof; the amount of polyacrylamide can be 14%, 14.5%, 15%, 15.5%, 16% or any two thereof. Regulating the amount of polyvinyl alcohol and polyacrylamide within the above range is more conducive to improving the wet strength, high temperature strength and air permeability of the ceramic shell.

[0061] In a specific embodiment of the present invention, the particle size of the low sodium fused white corundum powder is 1-70 μm, and the sodium oxide content is less than 0.1 wt%. Furthermore, the aluminum oxide content in the low sodium fused white corundum powder is greater than 99.5 wt%. This is more helpful to avoid the formation of high temperature low melting points while ensuring high temperature strength, and improve the chemical stability of the shell surface layer.

[0062] In a specific embodiment of the present invention, the particle size distribution of the low-sodium fused white corundum powder in the surface layer slurry and the back layer slurry independently satisfies: ≤70μm accounts for 100wt%, ≤50μm accounts for 60wt%~80wt%, ≤20μm accounts for 30wt%~50wt%, and ≤5μm accounts for 5wt%~15wt%.

[0063] In a specific embodiment of the present invention, the particle size of the active α-Al2O3 powder is 0.5 to 10 μm, for example, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm or any two thereof. Further, the purity of the active α-Al2O3 powder is greater than 99.5 wt%. The use of active α-Al2O3 powder with high activity and low impurity content helps to improve the wet strength and high temperature strength of the ceramic shell and reduce the introduction of impurities.

[0064] In a specific embodiment of the present invention, the particle size of the calcined zircon powder is 2-50 μm, for example, 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any two thereof. Further, in the calcined zircon powder, the sum of the contents of ZrO2 and HfO2 is greater than 65 wt%, for example, 65.2 wt%, 65.5 wt%, 65.8 wt%, 66 wt%, 66.3 wt% or any two thereof.

[0065] In a specific embodiment of the present invention, the first binder includes silica sol. Further, in the first binder, the SiO2 content is 28wt% to 31wt%, for example, it can be 28wt%, 29wt%, 30wt%, 31wt% or any two of them; the micelle diameter is 8 to 16μm, for example, it can be 8μm, 10μm, 12μm, 14μm, 16μm or any two of them; the pH value is 9 to 10.5, for example, it can be 9, 9.5, 10, 10.5 or any two of them.

[0066] In a specific embodiment of the present invention, the second binder includes silica sol. Further, in the second binder, the SiO2 content is 20wt% to 30wt%, for example, it can be 20wt%, 22wt%, 25wt%, 28wt%, 30wt% or a range consisting of any two thereof; the micelle diameter is 8 to 20μm, for example, it can be 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm or a range consisting of any two thereof; the pH value is 9 to 10.5, for example, it can be 9, 9.5, 10, 10.5 or a range consisting of any two thereof.

[0067] In a specific embodiment of the present invention, the surface layer slurry and the back layer slurry further independently include a defoamer and / or a wetting agent. Further, the amount of the defoamer and the wetting agent is 0.05-0.1 parts and 0.02-0.08 parts, respectively. For example, the amount of the defoamer can be 0.05 parts, 0.08 parts, 0.1 parts, etc., and the amount of the wetting agent can be 0.02 parts, 0.05 parts, 0.08 parts, etc.

[0068] In a specific embodiment of the present invention, the defoaming agent includes at least one of n-octanol and n-butanol; and the wetting agent includes fatty alcohol polyoxyethylene ether.

[0069] In a specific embodiment of the present invention, the coating-4 cup viscosity of the surface layer slurry is 25 to 50 seconds, for example, it can be 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds or any two of them; the coating-4 cup viscosity of the back layer slurry is 10 to 30 seconds, for example, it can be 10 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds or any two of them. This further improves the uniformity of the slurry during the coating process.

[0070] In a specific embodiment of the present invention, the surface layer of the glazing sand is white corundum sand. Further, the particle size of the surface layer of the glazing sand is 80-100 mesh, for example, it can be 80 mesh, 85 mesh, 90 mesh, 95 mesh, 100 mesh or any two thereof.

[0071] In a specific embodiment of the present invention, the backing layer of the glazing sand is white corundum sand. Further, the particle size of the backing layer of the glazing sand is 16-60 mesh, for example, it can be 16 mesh, 20 mesh, 25 mesh, 30 mesh, 35 mesh, 40 mesh, 45 mesh, 50 mesh, 55 mesh, 60 mesh or any two thereof.

[0072] In a specific embodiment of the present invention, in the back layer of sand casting, the mesh number of the white corundum sand used in the first layer of sand casting is greater than the mesh number of the white corundum sand used in the second layer of sand casting. Further, the mesh number of the white corundum sand used in the first layer of sand casting is 30 to 60 meshes, and the mesh number of the white corundum sand used in the second layer of sand casting is 16 to 24 meshes. Further, the mesh number of the white corundum sand used in the second layer and subsequent layers of sand casting is the same.

[0073] In a specific embodiment of the present invention, the dewaxing is steam dewaxing. Further, the steam dewaxing includes: dewaxing at 0.6-0.7 MPa and 165-175° C. for 15-30 min. The specific dewaxing process can be carried out in a high-pressure steam dewaxing kettle.

[0074] In a specific embodiment of the present invention, during the calcination, the temperature is 850-1050°C, for example, 850°C, 900°C, 950°C, 1000°C, 1050°C or any two thereof; the time is 3-6h, for example, 3h, 4h, 5h, 6h or any two thereof. Further, the calcination includes: calcining at 850-1050°C for 3-6h in an air atmosphere, cooling the furnace to below 500°C and taking it out.

[0075] A second aspect of the present invention provides a ceramic shell, which is prepared by any method for preparing a ceramic shell in the first aspect.

[0076] The third aspect of the present invention provides the use of the ceramic shell of the second aspect in manufacturing single crystal high temperature alloy turbine blades, wherein the single crystal high temperature alloy includes but is not limited to DD416, DD5 and the like.

[0077] Example 1

[0078] This embodiment provides a method for preparing a ceramic shell, comprising the following steps:

[0079] (1) Preparation of surface slurry:

[0080] Weigh 10 parts of silica sol, 30 parts of low-sodium fused white corundum powder, 1.5 parts of active α-Al2O3 micropowder, 0.5 parts of the first reinforcing agent, 0.05 parts of n-octanol, and 0.04 parts of fatty alcohol polyoxyethylene ether for later use according to weight; first pour the 1030C sol into the paint bucket, turn on the mixer and add the first reinforcing agent, fatty alcohol polyoxyethylene ether, and n-octanol in turn, stir for 15 minutes, then slowly add the active α-Al2O3 micropowder under stirring, stir for 0.5 hours, finally add the low-sodium fused white corundum powder and continue stirring for 3 hours to complete the preparation of the shell surface slurry; during this period, use the Tu-4 viscosity cup to test the viscosity of the surface slurry, and the viscosity is controlled at 35-40s.

[0081] The silica sol is Nalco silica sol, with a SiO2 content of 30wt%, a micelle diameter of 14μm, and a pH value of 10.26;

[0082] The low-sodium fused white corundum powder has an alumina content of 99.85wt% and a Na2O content of less than 0.1wt%; the particle size of the low-sodium fused white corundum powder is 1 to 70μm, and the particle size distribution satisfies: ≤50μm accounts for 70wt%, ≤20μm accounts for 40wt%, and ≤5μm accounts for 10wt%;

[0083] The active α-Al2O3 powder has an alumina content greater than 99.5wt%, a Na2O content less than 0.1wt%, and a particle size distribution of 2 to 6μm;

[0084] The first reinforcing agent includes, by mass percentage, 5% polyvinyl alcohol, 15% polyacrylamide and the balance deionized water.

[0085] (2) Preparation of backing layer slurry:

[0086] Weigh 10 parts of silica sol, 22 parts of low-sodium fused white corundum powder, 3 parts of calcined zircon powder, 0.8 parts of the second reinforcing agent, 0.03 parts of n-octanol, and 0.02 parts of fatty alcohol polyoxyethylene ether respectively by weight for later use; first pour the 1030C sol into the coating bucket, turn on the mixer and add the second reinforcing agent, fatty alcohol polyoxyethylene ether, and n-octanol in sequence, stir for 15 minutes, then slowly add the calcined zircon powder under stirring conditions, stir for 0.5 hours, finally add the low-sodium fused white corundum powder and continue stirring for 2 hours to complete the preparation of the shell back layer slurry; during this period, use the Tu-4 viscosity cup to test the viscosity of the back layer slurry, and the viscosity is controlled at 20-25 seconds;

[0087] The silica sol used in the back layer slurry is the same as the silica sol used in the surface layer slurry;

[0088] The composition, particle size and particle size distribution of the low sodium fused white corundum powder used in the back layer slurry are the same as those of the low sodium fused white corundum powder used in the surface layer slurry;

[0089] The calcined zircon powder has a ZrO2+HfO2 content of 66.3wt% and a particle size distribution of 2 to 45μm;

[0090] The second enhancer is the same as the first enhancer.

[0091] (3) Coating shell:

[0092] Surface coating: Use a manipulator to hold the handle of the molten mold module, slowly immerse the molten mold module into the above-prepared surface slurry, and after being completely immersed in the slurry for 10 to 15 seconds, lift the molten mold out of the slurry liquid surface, and perform slurry control and slurry throwing (rotating at a speed of about 15 to 25 r / min) operations to evenly coat the slurry on the surface of the molten mold. Transfer the module to the sand spraying machine for sand spraying, and evenly sprinkle 80 mesh white corundum sand on the surface slurry on the surface of the molten mold for 10 to 15 seconds. Naturally dry the sanded module for 6 hours to complete the preparation of the surface layer.

[0093] Back layer coating: First, spray the naturally dried surface layer to remove the floating sand on the surface layer, and then immerse it in the back layer slurry for slurry coating. After immersion for 2 to 3 seconds, the slurry liquid surface is raised to control the slurry and throw the slurry (rotate at a speed of about 15 to 25 r / min). Then the module is immersed in the sand spraying machine for sand coating, and the operation refers to the surface layer sand coating. After sand coating, fully dry under ventilation conditions for 10 hours. Repeat the process of slurry coating, sand spraying, and drying 5 times. After the sixth time of slurry coating using the back layer slurry as mentioned above, no sand coating operation is performed and drying is carried out directly. The first layer of sand coating on the back layer uses 46 mesh white corundum sand, and the second to fifth layers all use 24 mesh white corundum sand.

[0094] (4) Dewaxing and roasting:

[0095] The shell mold obtained in step (3) is placed in a high-pressure steam dewaxing kettle for steam dewaxing, with the pressure controlled at 0.65 MPa, the temperature at 170°C, and the dewaxing time being 20 minutes; the dewaxed shell mold is placed in a resistance furnace, and is calcined at 1000°C in an air atmosphere for 5 hours, and then cooled to below 500°C in the furnace and taken out to complete the preparation of the ceramic shell mold.

[0096] Example 2

[0097] This embodiment refers to the method for preparing the ceramic shell of Embodiment 1, with the only difference being that the surface layer slurry and the back layer slurry have different compositions, and the surface layer and back layer sanding types are different.

[0098] In this embodiment, the raw materials of the surface slurry include: 10 parts of silica sol, 38 parts of low-sodium fused white corundum powder, 1.9 parts of active α-Al2O3 micropowder, 0.4 parts of the first reinforcing agent, 0.03 parts of n-butanol, and 0.04 parts of fatty alcohol polyoxyethylene ether by weight; the particle size of the low-sodium fused white corundum powder is 1 to 70 μm, and the particle size distribution satisfies: ≤50 μm accounts for 60wt%, ≤20 μm accounts for 30wt%, and ≤5 μm accounts for 5wt%. The surface layer sanding adopts 100 mesh white corundum sand. The rest is the same as Example 1.

[0099] In this embodiment, the raw materials of the back layer slurry include: 10 parts of silica sol, 25 parts of low sodium fused white corundum powder, 3 parts of calcined zircon powder, 0.6 parts of the second reinforcing agent, 0.04 parts of n-octanol, and 0.02 parts of fatty alcohol polyoxyethylene ether in parts by weight; the particle size of the low sodium fused white corundum powder is 1 to 70 μm, and the particle size distribution satisfies: ≤50 μm accounts for 60wt%, ≤20 μm accounts for 30wt%, and ≤5 μm accounts for 5wt%. The first layer of the back layer sanding uses 60 mesh white corundum sand, and the second to fifth layers all use 16 mesh white corundum sand. The rest is the same as Example 1.

[0100] Example 3

[0101] This embodiment refers to the method for preparing the ceramic shell of Embodiment 1, with the only difference being that the surface layer slurry and the back layer slurry have different compositions, and the surface layer and back layer sanding types are different.

[0102] In this embodiment, the raw materials of the surface slurry include: 10 parts of silica sol, 25 parts of low-sodium fused white corundum powder, 1.2 parts of active α-Al2O3 micropowder, 0.5 parts of the first reinforcing agent, 0.03 parts of n-butanol, and 0.06 parts of fatty alcohol polyoxyethylene ether by weight; the particle size of the low-sodium fused white corundum powder is 1 to 70 μm, and the particle size distribution satisfies: ≤50 μm accounts for 80wt%, ≤20 μm accounts for 50wt%, and ≤5 μm accounts for 15wt%. The surface layer sanding adopts 90 mesh white corundum sand. The rest is the same as Example 1.

[0103] In this embodiment, the raw materials of the back layer slurry include: 10 parts of silica sol, 15 parts of low sodium fused white corundum powder, 5 parts of calcined zircon powder, 0.6 parts of the second reinforcing agent, 0.04 parts of n-octanol, and 0.02 parts of fatty alcohol polyoxyethylene ether in parts by weight; the particle size of the low sodium fused white corundum powder is 1 to 70 μm, and the particle size distribution satisfies: ≤50 μm accounts for 80wt%, ≤20 μm accounts for 50wt%, and ≤5 μm accounts for 15wt%. The first layer of the back layer sanding uses 50 mesh white corundum sand, and the second to fifth layers all use 20 mesh white corundum sand. The rest is the same as Example 1.

[0104] Example 4

[0105] This embodiment refers to the method for preparing the ceramic shell of Embodiment 1, with the only difference being that the compositions of the first reinforcing agent and the second reinforcing agent are different.

[0106] The first reinforcing agent and the second reinforcing agent of this embodiment both include, by mass percentage, 7.5% polyvinyl alcohol, 7.5% polyacrylamide, and the balance deionized water.

[0107] Example 5

[0108] This embodiment refers to the method for preparing the ceramic shell of Embodiment 1, with the only difference being that the compositions of the first reinforcing agent and the second reinforcing agent are different.

[0109] The first reinforcing agent and the second reinforcing agent of this embodiment both include, by mass percentage, 2.5% polyvinyl alcohol, 12.5% ​​polyacrylamide, and the balance deionized water.

[0110] Comparative Example 1

[0111] Comparative Example 1 refers to the method for preparing the ceramic shell of Example 1, except that the composition of the surface layer slurry and the back layer slurry are different.

[0112] In Comparative Example 1, the raw materials of the surface slurry include: 10 parts by weight of silica sol (brand JIN30, SiO2 content 28wt% to 30wt%, pH 9.3), 32 parts of EC95 powder, 0.05 parts of n-butanol, and 0.03 parts of fatty alcohol polyoxyethylene ether;

[0113] Among them, EC95 powder includes 94.6% Al2O3, 4.8% SiO2, 0.3% Na2O, 0.18% Fe2O3, and the rest are trace impurities such as CaO, MgO, Cr2O3, etc.; the particle size of EC95 powder is 1-70μm, and the particle size distribution satisfies: ≤55μm accounts for 70wt%, ≤18μm accounts for 20wt%, and ≤5μm accounts for 10wt%.

[0114] In Comparative Example 1, the raw materials of the back layer slurry include: 10 parts by weight of silica sol (brand name JIN30, SiO2 content 28wt%~30wt%, pH value 9.3), 20 parts of EC95 powder, 1.8 parts of kaolin, 0.2 parts of calcium carbonate, 0.05 parts of n-octanol, and 0.02 parts of fatty alcohol polyoxyethylene ether for standby use; the composition and particle size distribution of EC95 powder are the same as those of EC95 powder used in the surface layer slurry.

[0115] Comparative Example 2

[0116] Comparative Example 2 refers to the method for preparing the ceramic shell of Example 1, except that the compositions of the first reinforcing agent and the second reinforcing agent are different.

[0117] The first reinforcing agent and the second reinforcing agent of Comparative Example 2 both include 15% by mass of polyvinyl alcohol and the balance of deionized water.

[0118] Comparative Example 3

[0119] Comparative Example 3 refers to the method for preparing the ceramic shell of Example 1, except that the compositions of the first reinforcing agent and the second reinforcing agent are different.

[0120] The first reinforcing agent and the second reinforcing agent of Comparative Example 3 both include 15% by mass of polyacrylamide and the balance of deionized water.

[0121] Experimental Example 1

[0122] The thickness, wet strength, room temperature strength after shell baking, high temperature strength at 1550°C and air permeability at 1550°C of the ceramic shells of different embodiments and comparative examples were tested. The test results are shown in Table 1.

[0123] Among them, wet strength refers to the strength of the ceramic shell after dewaxing; room temperature strength after shell baking refers to the strength of the ceramic shell after calcining and cooling to room temperature; 1550℃ high temperature strength refers to the strength of the prepared ceramic shell at 1550℃; permeability at 1550℃ refers to the amount of gas passing through unit area of ​​the shell per unit time at 1550℃ and 1Pa pressure difference. The test reference standard is HB5352.4-2004 "Test Method for Performance of Investment Casting Shell": Part 4: Determination of Permeability.

[0124] Table 1 Test results of different ceramic shells

[0125]

[0126] Figure 2 This is a thickness comparison diagram of the ceramic shell prepared in Example 1 of the present invention and the EC95 shell of Comparative Example 1. The left side is the ceramic shell of Comparative Example 1, and the right side is the ceramic shell of Example 1. Figure 2 It can be seen that the ceramic shell prepared in the embodiment of the present invention has a thinner thickness and better air permeability under the same number of coating layers; and the wet strength of the ceramic shell prepared in the embodiment of the present invention is better than that of the comparative example, which is beneficial to improving the qualified rate of the ceramic shell; the ceramic shell prepared in the embodiment of the present invention has higher high-temperature strength and meets the more stringent requirements of single crystal alloy casting.

[0127] Experimental Example 2

[0128] The ceramic shells of Example 1 and Comparative Example 1 of the present invention were used to cast DD416 single crystal blades under the same conditions. The casting temperature was 1550-1560°C. The photos of the high-temperature alloy parts obtained by casting are shown in FIG. Figure 3 and Figure 4As shown in the figure, the casting blade made by using the ceramic shell of Example 1 has a good surface, no steel leakage at the weak part of the edge plate, and the R angle of the blade crown is not loose when the fluorescence shows it; the casting blade made by using the ceramic shell of Comparative Example 1 has steel leakage at the weak part of the edge plate, and the R angle of the blade crown has loose defects.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a ceramic shell, characterized in that: The steps include: (a) coating the surface layer slurry on the investment mold group, then pouring sand and drying to form the surface layer; (b) coating the surface layer with a backing layer slurry, sprinkling sand, and drying the surface layer N times to form a backing layer; and sealing the slurry to obtain a wet blank; N≥2; (c) dewaxing and calcining the wet blank to obtain the ceramic shell; The surface layer slurry includes the following components by weight: 10 parts of a first binder, 25 to 38 parts of low-sodium fused white corundum powder, 1 to 2 parts of active α-Al2O3 powder and 0.2 to 1.5 parts of a first reinforcing agent; The backing layer slurry comprises the following components by weight: 10 parts of a second binder, 15 to 25 parts of low-sodium fused white corundum powder, 1 to 5 parts of calcined zircon powder, and 0.2 to 1.5 parts of a second reinforcing agent; The first reinforcing agent and the second reinforcing agent each independently include polyvinyl alcohol, polyacrylamide and water.

2. The method for preparing a ceramic shell according to claim 1, characterized in that: In the first enhancer and the second enhancer, the mass ratio of the polyvinyl alcohol to the polyacrylamide is independently 1:(1-5); Preferably, the first reinforcing agent and the second reinforcing agent each independently include, by mass percentage, 4% to 6% polyvinyl alcohol, 14% to 16% polyacrylamide and 78% to 82% water.

3. The method for preparing a ceramic shell according to claim 1, characterized in that: The low-sodium fused white corundum powder has a particle size of 1 to 70 μm and a sodium oxide content of less than 0.1 wt%; Preferably, the low-sodium fused white corundum powder has an alumina content of >99.5wt%.

4. The method for preparing a ceramic shell according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The particle size of the active α-Al2O3 powder is 0.5 to 10 μm; (2) The purity of the active α-Al2O3 powder is greater than 99.5wt%; (3) The particle size of the calcined zircon powder is 2 to 50 μm; (4) In the calcined zircon powder, the sum of the contents of ZrO2 and HfO2 is greater than 65 wt%.

5. The method for preparing a ceramic shell according to claim 1, characterized in that: The first binder includes silica sol; Preferably, in the first binder, the SiO2 content is 28wt% to 31wt%, the micelle diameter is 8 to 16 μm, and the pH value is 9 to 10.5; Preferably, the second binder comprises silica sol; Preferably, in the second binder, the SiO2 content is 20wt% to 30wt%, the micelle diameter is 8 to 20 μm, and the pH value is 9 to 10.

5.

6. The method for preparing a ceramic shell according to claim 1, characterized in that: The surface layer slurry and the back layer slurry also independently include a defoamer and / or a wetting agent; Preferably, the defoaming agent and wetting agent are used in amounts of 0.05-0.1 parts by weight and 0.02-0.08 parts by weight, respectively.

7. The method for preparing a ceramic shell according to claim 1, characterized in that: The surface layer of sand is white corundum sand, and the back layer of sand is white corundum sand; Preferably, the particle size of the surface layer of sand is 80-100 mesh; Preferably, the particle size of the backing layer of sand is 16-60 mesh; Preferably, in the sand casting of the back layer, the mesh number of the white corundum sand used in the first layer of sand casting is greater than the mesh number of the white corundum sand used in the second layer of sand casting.

8. The method for preparing a ceramic shell according to claim 1, characterized in that: During the calcination, the temperature is 850-1050° C. and the time is 3-6 hours.

9. A ceramic shell, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Use of the preparation method according to claim 9 in manufacturing single crystal high temperature alloy turbine blades.